Ragnarǫk: alternativas de interpretação da escatologia escandinava - Stern, Fábio L. (Sacrilegens, 2016)
This study aims to provide other perspectives of interpretation of Ragnarǫk, the Scandinavian eschatological myth, instead of the common theory that it is a narrative about the replacement of the Norse religion by Christianity. After entering the Norse cosmology and Ragnarǫk myth, we present the discussions developed by authors who diverge from the common place concerning the interpretation of this myth. We identify two lines of analysis: one that considers the Ragnarǫk mythical narrative an allegory of historical past events and another that considers the Ragnarǫk narrative as a warning of the dangers of going against the values of the Norse society.